Tectonic significance of Late Ordovician granitic magmatism and clastic sedimentation on the northern margin of Gondwana (Tavsanli Zone, NW Turkey) - Ozbey, Zeynep; Ustaomer, Timur; Robertson, Alastair H. F.; Ustaomer, P. Ayda (GEOLOGICAL SOC PUBL HOUSE, 2013)
Metasedimentary schists and a small crosscutting metagranite underlie a Mesozoic metamorphosed carbonate platform within the regional Anatolide tectonic belt of northern Turkey. These lithologies are inferred to have formed part of the northern margin of Gondwana during the Palaeozoic. Immobile element geochemistry suggests that the country rock metasediments were derived from upper continental crust and arc-type magmatic rocks. Major and trace element analyses of the metagranite indicate affinities with upper continental crust or a continental margin magmatic arc. Tectonic discrimination of the metagranite is consistent with a rift or post-collisional setting. Niobium depletion relative to Ce on primitive mantle-normalized spidergrams suggests a subduction influence, possibly inherited from Late Precambrian (Cadomian) arc magmatism. Ion microprobe U-Pb dating of zircons from the metagranite yielded a crystallization age of 446 +/- 8 Ma (Late Ordovician). An inherited core gave a concordant age of c. 578 Ma, consistent with Cadomian or Pan-African basement. Regional comparisons indicate that the Palaeozoic lithostratigraphy is similar to that of the Taurides (Gondwana) rather than the Pontides (Laurasia). We infer Mid-to Late Ordovician crustal extension along the north Gondwana margin, followed by spreading of Palaeotethys. The entire stratigraphy experienced high-pressure/low-temperature metamorphism during Late Cretaceous closure of the Izmir-Ankara-Erzincan ocean.
Keywords: CRUSTAL EVOLUTION; METASEDIMENTARY ROCKS; GEOLOGICAL EVOLUTION; NORTHWEST TURKEY; STRANDJA MASSIF; SOUTHERN TURKEY; SUBDUCTION; VARISCAN; BASEMENT; GEOCHRONOLOGY; Geology